Determination of Indigenous Nutrient Supplying Capacity of Soil Through Omission Plot Experiment for Wheat in Western Terai of Nepal - Rawal, N.; Khatri, N.; GC, C. B.; Chaurasiya, B. P. (Journal of the Institute of Agriculture and Animal Science, 2018)
The field experiment was conducted to estimate the native nutrient supplying capacity of soil in western terai of Nepal during 2013/14 and 2014/15. The experimental site consisted three areas: Pakadi VDC ward no.-3, Barrohiya of Kapilvastu district; Ramgram municipality ward no.-1, Sanda of Nawalparasi district and Tukuligadh VDC ward no.-1, Rehara of Rupandehi district. The indigenous nutrients supplying capacity of the soil was determined by establishing omission plots for wheat cultivation with six treatments each of 50 m2 and 4 farmers from each site was taken assuming one farmer as one replication. Among the six treatments, -N, -P, -K, –Zn and –B were set to estimate the inherent N, P, K, Zn and B supplying capacity of soil respectively. From two years of experiment, it has been clear that inherent N and K supplying capacity of soil in selected areas is very low. The highest grain yield of 3.33 t/ha and 2.75 t/ha was measured from fully fertilized plots in 2013/14 and 2014/15 respectively and the lowest grain yield of wheat was obtained from nitrogen missing plots in both years (1.74 t/ha and 1.51 ton/ha) followed by potassium missing plots (1.74t/ha). Farmers manage their field in a different way, so large variation was seen even in small area. Nitrogen was found to be most limiting nutrient for wheat growth followed by potassium and phosphorous in all sites. Therefore, use of optimum dose of nitrogen, phosphorus and potassium should be used for efficient nutrient uptake which ultimately increases wheat productivity.